2013
DOI: 10.3839/jabc.2013.033
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment on Nitrate and Nitrite in Vegetables Available in Korean Diet

Abstract: Nitrate is a naturally occurring compound in plant and can be converted to nitrite in the nitrogen cycle and vice versa. Therefore, it is easy to find nitrate in plants including vegetables. Especially, it is known that high levels of nitrate found in leafy vegetables. Nitrate itself is relatively non-toxic but its metabolites and reaction products such as nitrite, nitric oxide and N-nitroso compounds, may produce adverse health effects such as methaemoglobinaemia and carcinogenesis. To execute the risk assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 3 publications
4
7
0
Order By: Relevance
“…The mean nitrate contents in CCP, RP, and SP were 44,077 ppm, 66,178 ppm, and 120,315 ppm, respectively, with SP showing the highest (p<0.05) nitrate content and CCP the lowest (p<0.05). These results were consistent with the trends of previous studies on fresh Chinese cabbage, radish, and spinach ( Chung et al, 2003 ; Suh et al, 2013 ). Suh et al (2013) observed that the nitrate content in Chinese cabbage, radish, and spinach collected from retail markets in Korea averaged 1,059.9 mg/kg, 1,494.0 mg/kg, and 2,123.8 mg/kg, respectively.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The mean nitrate contents in CCP, RP, and SP were 44,077 ppm, 66,178 ppm, and 120,315 ppm, respectively, with SP showing the highest (p<0.05) nitrate content and CCP the lowest (p<0.05). These results were consistent with the trends of previous studies on fresh Chinese cabbage, radish, and spinach ( Chung et al, 2003 ; Suh et al, 2013 ). Suh et al (2013) observed that the nitrate content in Chinese cabbage, radish, and spinach collected from retail markets in Korea averaged 1,059.9 mg/kg, 1,494.0 mg/kg, and 2,123.8 mg/kg, respectively.…”
Section: Resultssupporting
confidence: 93%
“…These results were consistent with the trends of previous studies on fresh Chinese cabbage, radish, and spinach ( Chung et al, 2003 ; Suh et al, 2013 ). Suh et al (2013) observed that the nitrate content in Chinese cabbage, radish, and spinach collected from retail markets in Korea averaged 1,059.9 mg/kg, 1,494.0 mg/kg, and 2,123.8 mg/kg, respectively. These results indicated that the nitrate concentration in vegetables was increased by the drying process in our study.…”
Section: Resultssupporting
confidence: 93%
“…In this study, the highest and lowest health risks were related for spinach and bean sprouts with a daily intake of 0.235 and 0.00 mg/kg/day, respectively. Many of the vegetables used in this research were not studied, but considering that the highest health risk was related to vegetables with the highest nitrate concentrations, the lowest health risk was related to vegetables with the lowest nitrate concentrations; therefore, the health risk is directly related to the nitrate concentrations in vegetables, and the results of that study are consistent with this study [48].…”
Section: Vegetable Typesupporting
confidence: 80%
“…Correia et al in an analysis of different varieties of vegetables, found nitrite concentrations ranged 0.11-5.4 mg 100 g -1 (Correia et al, 2010); Mor et al also reported a wide range of nitrite levels in vegetables especially in lettuce (0.29-0.88 mg 100 g -1 ), spinach (0.38-1.27 mg 100 g -1 ) and radish (0.24-1.42 mg 100 g -1 ) (Mor et al, 2010). Similarly, nitrite content of different vegetables in Denmark andGermany ranged 0.015-1.10 and <0.01-1.96 mg 100 g -1 , respectively; nitrite concentration of vegetables in a survey in Korea were also reported to range from 0.01 to 63.5 mg 100 g -1(Suh et al, 2013).…”
mentioning
confidence: 89%